Two Sides of a Coin: Effects of Perceived and Actual Financial Literacy on Investment Decision Making Behavior Mediated by Financial Risk Tolerance - Ahmed, Zaheer; Ramakrishnan, Suresh; Noreen, Umara (International Journal of Engineering and Technology, 2018)
Investment decision making is a complex phenomenon driven by the behavioral dimensions of investors, based on both the objective and subjective grounds, since investors are the humans. This is a qualitative research based on extensive literature review and develops a framework useful for future investors. This study explores the impact of perceived and actual financial literacy on financial risk tolerance and investment decision-making behavior of individual investors. Study also identifies the role of financial risk tolerance between the relationship of financial literacy (perceived and actual) and investment decision-making behavior. Based on extensive literature review, study concludes that harmonization among perceived and actual financial literacy of investors is necessary for making accurate decisions with minimum risk. Similarly, it identifies that high and sufficient financial literacy leads to better financial risk tolerance ability, therefore investors invest in risky securities confidently. Furthermore, study is a guideline for investors, professionals and households for improving their financial literacy. Also, it helps investor to identify level of financial literacy they required to deal with risky financial conditions and for making healthy investment decisions. Finally, study will help investors to make true evaluation of their actual financial knowledge to avoid overconfidence, a negative predictor of decision-making behavior.